Eltrombopag in Combination with Rabbit Anti-thymocyte Globulin/Cyclosporine A in Immunosuppressive Therapy-naïve Patients with Aplastic Anemia in Japan - Imada, Kazunori (Intern Med, 2020)
OBJECTIVE: In Japan, immunosuppressive therapy (IST) with anti-thymocyte globulin (ATG), and cyclosporine A (CsA) is the standard of care in patients with aplastic anemia (AA) who are not indicated for stem-cell transplantation, although some patients may experience relapse. This study assessed the efficacy and safety of eltrombopag in combination with rabbit-ATG/CsA in IST-naïve patients with non-severe or severe AA in Japan. METHODS: In this non-randomized, open-label, single-arm, phase II study, rabbit-ATG/CsA and eltrombopag were initiated on Days 1 and 15 (±3 days), respectively, and continued for ≥26 weeks; rabbit-ATG was given for 5 days (Days 1 to 5). The primary endpoint was the overall response rate (ORR) at Week 26. PATIENTS: Patients with AA who were IST-naïve and ≤70 years old or between 71 and 75 years old based on the recommendation of the investigator were enrolled in Japan. RESULTS: Of the 11 enrolled patients, 10 started treatment with eltrombopag. The ORRs at Weeks 26 and 52 were 70.0% and 60.0%, respectively. The ORR at Week 26 was 100% (all 3 patients) in patients with non-severe AA and 57.1% (4/7) in patients with severe AA. Among transfusion-dependent patients, 66.7% (4/6) and 62.5% (5/8) became red blood cell- and platelet-transfusion independent, respectively. The most common adverse events were nausea and headache. No deaths or hematologic malignancies were reported. A cytogenetic abnormality was reported in one patient. CONCLUSION: This study confirmed the clinical benefit of eltrombopag plus rabbit-ATG/CsA in IST-naïve patients with non-severe or severe AA in Japan.